ANALISIS KEGAGALAN PADA SEKSI MARKING UNTUK MENURUNKAN KLAIM INTERNAL DENGAN MENGAPLIKASIKAN METODE PDCA - Sofian Bastuti (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2017)
Industrial development requires the company to continual improvement of product quality in order to survive and lead the market. In this study, the authors analyzed the internal quality claims section as  the highest marking by alternative repair using PDCA approach with seventools. This study used quantitative data, qualitative and descriptive exploratory analysis. Based on the results of repair, marking sexy internal claims decreased from 73 claims to 26 claims or if calculated on average before repair and after repair claims 6:08 3:25 claims decreased by 53%.